2022
DOI: 10.3390/ma15124209
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Steel Fiber-Reinforced Concrete Employing Supervised Machine Learning Techniques

Abstract: Recently, research has centered on developing new approaches, such as supervised machine learning techniques, that can compute the mechanical characteristics of materials without investing much effort, time, or money in experimentation. To predict the 28-day compressive strength of steel fiber–reinforced concrete (SFRC), machine learning techniques, i.e., individual and ensemble models, were considered. For this study, two ensemble approaches (SVR AdaBoost and SVR bagging) and one individual technique (support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…For the prediction of CS behavior of NC, Kabirvu et al 5 implemented SVR, and observed that SVR showed high accuracy (with R 2 = 0.97). Whereas, Koya et al 39 and Li et al 54 reported that SVR showed a high difference between experimental and anticipated values in predicting the CS of NC. Based on the results obtained from the implementation of SVR in predicting the CS of SFRC and outcomes from previous studies in using the SVR to predict the CS of NC and SFRC, it was concluded that in some research, SVR demonstrated acceptable performance.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the prediction of CS behavior of NC, Kabirvu et al 5 implemented SVR, and observed that SVR showed high accuracy (with R 2 = 0.97). Whereas, Koya et al 39 and Li et al 54 reported that SVR showed a high difference between experimental and anticipated values in predicting the CS of NC. Based on the results obtained from the implementation of SVR in predicting the CS of SFRC and outcomes from previous studies in using the SVR to predict the CS of NC and SFRC, it was concluded that in some research, SVR demonstrated acceptable performance.…”
Section: Resultsmentioning
confidence: 96%
“…Also, the characteristics of ISF (V ISF , L/D ISF ) have a minor effect on the CS of SFRC. Li et al 54 noted that the CS of SFRC increased with increasing amounts of C and silica fume, and decreased with increasing amounts of water and SP. Therefore, based on the sensitivity analysis, the ML algorithms for predicting the CS of SFRC can be deemed reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…The reinforced concrete (RC) evolution have been an ongoing process with so many advancements (Ahmad et al, 2022;Ahmed et al, 2022;Ali et al, 2022;Ashraf et al, 2022;Ghareeb et al, 2022;Huang et al, 2022;Khan et al, 2022;Li et al, 2022;Mohammed et al, 2022;Shen et al, 2022;Zou et al, 2023a;Zou et al, 2023b). High-strength concrete (HSC), especially that with fiber-RC (FRC) is a versatile form of a concrete mixture with superior performance compared to that of normal RC without fiber reinforcement (Deifalla, 2021a;Deifalla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to predict concrete strength characteristics [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Machine learning methods are employed to forecast concrete strength [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and the durability of concrete [ 50 , 51 , 52 ]. Bagging regression (BR) and gradient boosting (GB) models based on a variation of the bootstrap aggregation decision tree (DT) method have been shown in several studies to outperform other stand-alone ML models in terms of concrete strength prediction accuracy [ 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%